The Use of Padlet Application as a Reflection Tool for Science Teachers' Teaching Practice: A Mixed Methods Study - Sri Wahyuni; Wirawan Fadly (Universitas Pendidikan Mandalika, 2025)
Many science teachers have not yet used reflection as a means of learning evaluation, making it difficult for them to identify problems and find solutions. They also face challenges in determining the right medium for reflection. This study aims to explore the use of Padlet as a reflection tool for science teachers. A mixed-method approach was employed, involving three science teachers as qualitative data sources and 52 students as quantitative research subjects, divided into two classes. Data analysis was conducted using N-Vivo for qualitative data and SPSS for quantitative data, with t-tests and N-Gain tests applied to test the hypotheses. The results indicate that all three teachers agreed that using Padlet significantly improves learning quality. Quantitative data confirms the effectiveness of Padlet in enhancing reflective skills, with a t-test result of 0.000 and an N-Gain score of 75%. These figures indicate that learning with Padlet, integrated with the Group Investigation model in the experimental class, is categorized as effective. This study serves as a reference for science teachers to innovate in using technology for learning reflection, as Padlet has been proven to facilitate reflection for both teachers and students in science education.